Improving Reading Comprehension Skills Through the Scramble Techniques Using Picture Storybook Media at Grade VI Deaf Students SLB B Prima Bhakti Mulia Cimahi - Eliskar, Nelvi Roza; Susetyo, Budi; Aprilia, Imas Diana (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Reading is one of the language skills that has an important role in improving the quality of one's life. One of the reading skills that children must master is reading comprehension. Deaf children have low reading comprehension skills. To overcome low reading comprehension skills, it is considered necessary to provide an alternative learning, one of which is given an alternative use of scramble techniques with picture story book media. The purpose of this study was to determine how much the improvement in reading comprehension skills in grade VI deaf students at SLB B Prima Bhakti Mulia Cimahi through the use of scramble techniques with picture story book media. The method used in this study is a qualitative method with the subject of research as many as 5 grade VI students. The results showed that there was an increase in reading comprehension skills in grade VI deaf students using scramble techniques through picture story book media. The use of scramble techniques with picture storybook media in reading comprehension activities can focus students' attention on the material given, and cause greater curiosity. So that reading comprehension skills in deaf students become improved in a better direction.